2021
DOI: 10.5606/e-cvsi.2021.1076
|View full text |Cite
|
Sign up to set email alerts
|

Patient and healthcare provider burden due to conventional measurement of the international normalized ratio: From a multi-dimensional perspective

Abstract: In this study, we aimed to investigate the healthcare burden associated with hospital visits for international normalized ratio (INR) measurement from a multi-dimensional perspective.Patients and methods: A total of 415 patients (198 males, 217 females; mean age: 54±12.7 years; range, 14 to 84 years) who were admitted to the cardiovascular surgery (CVS) outpatient clinic between March 2015 and June 2015 were included. The burden of INR measurement was assessed in two main categories: social and clinical. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…It was reported that the rate of major bleeding complications was reported between 1.0 and 2.36 in 100 patients using warfarin. [14,15] In the study of Kavasoglu et al, [16] which included 415 patients using warfarin, the rate of major bleeding was reported as 2.6%.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the rate of major bleeding complications was reported between 1.0 and 2.36 in 100 patients using warfarin. [14,15] In the study of Kavasoglu et al, [16] which included 415 patients using warfarin, the rate of major bleeding was reported as 2.6%.…”
Section: Discussionmentioning
confidence: 99%